PORFAVOR PARA AHORITA :)
Adjuntos:
![](https://es-static.z-dn.net/files/dca/7b7c8d4d83f0aa5b61fdc81e812da7d8.jpeg)
america1992:
fjre tghojnretowrneto5henibegout4eiotgyh4ibtuw4rtjfgbrueig5ue9ptgpo5gue
Respuestas
Respuesta dada por:
2
Respuesta:
Respuesta D) 4
Explicación paso a paso:
- tg(x+y) = cotg 40º
tg(x+y) = 1,19
x+y = tg⁻¹ (1,19)
x+y = 50 ⇒ x = 50 - y
- sen(x-y) . cosec 30º = 1
sen(x-y) . 2 = 1
sen(x-y) = 1/2
x - y = sen⁻¹ (1/2)
x - y = 30º Reemplazando:
50 - y - y = 30
50 - 2y = 30
50 - 30 = 2y
20 = 2y
20 : 2 = y
10º = y
x = 50 - 10
x = 40º
- x/y = 40º/10º
x/y = 4
Preguntas similares
hace 4 años
hace 7 años
hace 7 años
hace 8 años